Mali : Joint Staff Assessment of Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) for Mali. The PRSP finalized by the Malian authorities in May 2002 presents a credible policy framework to reduce poverty. The PRSP acknowledges the need for further work to systematize participation and consensus building in the management of public affairs and to strengthen and sustain the consultation process with the poor. The authorities have started addressing these needs by reorienting the working groups and other institutional structures that prepared the PRSP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet